Cuento folklórico y narrativa oral : versiones, variantes y estudios de génesis - María Inés Palleiro (Cuadernos LIRICO)
In this article, I propose an approach to oral narrative from a genetic perspective, linking the versions and variants of folktale with textual variants studied by genetic criticism. The theoretical guidelines combine genetic concepts such as “textual genesis” with those of hypertext theory. In order to explain such proposal, I analyse alternative itineraries of the folk narrative matrix “Strong John” (ATU 650 A), by means of an intertextual comparison of different versions both in rural and urban contexts. As a point of departure, I analyse the version “Juan Catorce” by Andrea Cerda, collected in the Argentine province of La Rioja. Then I examine an alternative itinerary in an urban written version of the legend of the Golem set in Buenos Aires. At last, I consider a literary recreation in the poem “El Golem” by Jorge Luis Borges. The aim of this approach is to highlight the dispersive itineraries of folk narrative matrices, and the dynamics between oral and written culture.